Pectins from fruits: Relationships between extraction methods, structural characteristics, and functional properties. (April 2021) - Cui, Jiefen; Zhao, Chengying; Feng, Liping; Han, Yanhui; Du, Hengjun; Xiao, Hang; Zheng, Jinkai
Abstract: Background: Fruits are the main source of pectin, with more than 90% of commercial pectins being derived from fruit by-products. Fruit pectins are complex heterogeneous polysaccharides that exhibit a variety of physicochemical properties and health functions. Fruit pectins exist in the primary cell walls and middle lamella of plants and are usually crosslinked with cellulose and hemicellulose; their extraction involves hydrolysis, isolation, and solubilization processes. Conventional studies have focused solely on individual extraction methods, structural characteristics, or functional properties, while neglecting the relationships between these factors. Scope and approach: This review systematically summarizes the principles and features of single, i.e., acid, alkali, and enzymatic digestion, and combined, i.e., subcritical water, ultrasound-, microwave-, and ultrasound-microwave-assisted, methods for extracting pectins from fruit. We discuss the effects of different extraction methods on the structural characteristics of fruit pectins including molecular weight, monosaccharide composition, degree of esterification, and conformation. The impacts of these structural characteristics on the physicochemical properties and health functions, specifically the regulation of gut microbiota and anti-inflammatory, antiglycation, and immunomodulating effects of fruit pectins are also discussed. Key findings and conclusions: Different extraction methods result in pectins with different structural characteristics. These, in turn, strongly affect the physicochemical properties and health functions of the pectin. Therefore, a comprehensive understanding of the extraction-structure-property relationships of pectin is crucial to realizing pectin preparations with targeted functional effects. Highlights: Features of different extraction methods of fruit pectins were summarized. Effects of extraction methods on pectin structural characteristics were discussed. Impacts of structural characteristics on functional properties were explored. Relationships between extraction, structure and properties of pectins were emphasized.